2008
DOI: 10.1177/104063870802000605
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Enzyme-Linked Immunosorbent Assays to Detect Porcine Circovirus-2 (PCV-2)—Specific Antibodies after Vaccination or Inoculation of Pigs with Distinct PCV-1 or PCV-2 Isolates

Abstract: Abstract. Porcine circovirus-2 (PCV-2) serology is frequently used to determine PCV-2 status and optimal timing of PCV-2 vaccination in the field. The objectives of the current study are to determine the diagnostic accuracy of 3 currently available commercial anti-immunoglobulin G (IgG) PCV-2 enzyme-linked immunosorbent assays (ELISAs) and to compare the ability of the 3 assays to detect and differentiate between anti-PCV-2a and anti-PCV-2b antibodies, as well as anti-PCV-2 and anti-PCV-1 antibodies. Fiftyfive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…However, the analysis of PCV2-specific antibody titres is challenging from a technical perspective. Several studies revealed that vast differences among laboratories and various ELISA test systems exist [29,30]. Despite these issues, we decided to use a qualitative ELISA capable of distinguishing IgM from IgG antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the analysis of PCV2-specific antibody titres is challenging from a technical perspective. Several studies revealed that vast differences among laboratories and various ELISA test systems exist [29,30]. Despite these issues, we decided to use a qualitative ELISA capable of distinguishing IgM from IgG antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were considered positive if the calculated sample-to-positive (S/P) ratio was 0.2 or greater. Previously, this ELISA has shown to have a sensitivity and specificity of 100% at the S/P ratio 0.2 cutoff using samples from experimentally infected pigs on trial day 49 [41]. …”
Section: Methodsmentioning
confidence: 99%
“…In some cases, PCVs were detected simultaneously with other porcine viruses using multiplex PCR [51,52]. Other detection methods are antibody-based methods such as enzyme-linked immunosorbent assay (ELISA), Western blot analysis, and immunofluorescence [53,54,55,56,57,58]. The use of saliva for antibody detection gained popularity because of the ease of use and associated cost-saving [59].…”
Section: Diagnosis and Transmissionmentioning
confidence: 99%